The Penerapan Metode Just In Time (JIT) Dalam Pengendalian Persediaan Budidaya Ikan Lele Untuk Meminimalkan Biaya Persediaan - Syahputra, Fakhri Ananda; Dur, Sajaratud; Rakhmawati, Fibri (TIN: Terapan Informatika Nusantara, 2022)
Catfish farming is a business that is engaged in the fishing industry. An activity in which people raise catfish (including spawning, breeding, etc.) to be sold. Therefore, the just in time method is used to minimize costs by planning the inventory calculation of the cost of catfish cultivation needs such as seeds, marketing, raw materials so that costs are more optimal and market supplies more controlled. After analyzing the total cost of inventory in Pak Dedy Santoso catfish farming, it can be concluded that in the company's calculation method the level of raw material requirements is 6000 kg, with 12 times the quantity of delivery, the total cost of raw material inventory in catfish farming is Rp. 2,670. 750.00. Whereas in the calculation of the Just In Time system, namely delivery of 85 times with a total inventory cost of Rp. 289,684, - and it can be seen that the cost savings obtained are Rp. 2,381,066. Then about the tolerance value for defects, damage, loss, and others by 5%. At the inventory level of 6000 kg, assuming a tolerance level of 5%, it is known that the inventory in the company's calculation is 6,300 kg